Agrophysical properties of soil (Texas Journal of Agriculture and Biological Sciences, 2025)
IN The article presents analytical data on irrigated meadow-marsh soils; the first watering is carried out before the plant blooms (based on a soil layer of 0-50 cm) at the rate of 700-750 m3 / ha of water; in the early stages of the cotton growth period, the layer should not exceed 0-70 cm, and the watering rate is 850-900 m3 / ha